Improving logistics visibility in a supply chain: an integrated approach with radio frequency identification technology. (8th January 2007) - Choy, K.L.; So, Stuart C.K.; Liu, John J.; Lau, Henry; , S.K. Kwok
Third Party Logistics (3PL) becomes more important nowadays as it aims to improve supply chain efficiency through reducing cycle time and inventory level for both upstream suppliers and downstream retailers. However, many small to medium-sized 3PL providers in the Pearl River Delta (PRD) region still highly rely on manual processes, which make them difficult to achieve the role of supply chain facilitators. In this study, a logistics information hub named Integrated Logistics Information Management System (ILIMS) adopting Radio Frequency Identification (RFID) technology is presented to suit this need. With ILIMS, 3PL companies are provided with unified business processes with enhanced tracking capability. A case study is discussed in applying ILIMS to a medium-sized 3PL company. Through using this generic system, the logistics visibility in the supply chain is improved with significant reduction of delivery time, supply cost, inventory and out-of-stock frequency that lead to increase of revenue and operations volume.